DISPLACING THE ANXIETIES OF OUR WORLD. - LIMPAR, ILDIKO (CAMBRIDGE SCHOLARS PUBLIS, 2017)
Monster studies, dystopian literature and film studies have become central to research on the now-proliferating works that give voice to culture-specific anxieties. This new development in scholarship reinforces the notion that the genres of fantasy and science fiction call for interpretations that see their spaces of imagination as reflections of reality, not as spaces invented merely to escape the real world. In this vein, Displacing the Anxieties of Our World discusses fictive spaces of literature, film, and video gaming. The eleven essays that follow the Introduction are grouped into four.